A comparison between Web Service and JAVA Message Service technologies for Event-Driven Mashup execution. (13th September 2010) - Stecca, Michele; Maresca, Massimo
This paper presents a Service Execution Platform (SEP) for Event-Driven service compositions (a.k.a. Mashups), typically used in domains characterised by a working principle based on asynchronous events. The platform reference model is based on an orchestration system and on a set of Service Proxies (SPs) hosted in the SEP. The orchestration system executes Mashup Sessions by coordinating the actions of the SPs, and takes care of load balancing, security (AAA) and fault tolerance. The paper presents and compares two versions of the SEP based on two different technologies, namely Web Services (WSs) and JAVA Message Service (JMS).